Vicarious Liability under the Indonesian Criminal Code: A Living Law Perspective from Yogyakarta: Vicarious Liability Dalam KUHP Nasional Dikaji dari Perspektif Living Law di Yogyakarta - Sahran Hadziq; Gatot Sugiharto (Lex Renaissance, 2024)
The National Criminal Code as the brand-new Indonesian criminal law’s face provides several fundamental changes, including provisions on the principle of material legality and vicarious liability. The principle of material legality provides space for living law to be the basis for the implementation of criminal law, including in determining criminal liability. Vicarious liability is a form of criminal liability that eliminates mistakes and is interpreted as substitute liability, namely that everyone can be held accountable for the actions of others. The perspective of living law is essentially very broad so each society has different characteristics and provisions. Provisions on vicarious liability based on living law can be found in the early civil law as a form of living law in Yogyakarta. This study aims to provide an understanding of the regulation of vicarious liability in Indonesian criminal law and to examine the regulation of vicarious liability based on the perspective of living law contained in early civil law. This study is an empirical legal study using a historical and philosophical approach. The data used in this study are primary and secondary data using interview methods and literature studies which are then analyzed descriptively qualitatively. The results of this study explain the differences in understanding of vicarious liability. Indonesian criminal law through the National Criminal Code understands vicarious liability only as a "command" responsibility, while the living law perspective in the early civil law understands vicarious liability as an effort to restore balance in cosmic life that is damaged by someone's actions. The recommendation in this study is that there needs to be an additional explanation of vicarious liability in the National Criminal Code so that it is in line with living law.Keywords: Angger Perdata Awal, Indonesian Criminal Law, Living Law, Vicarious Liability AbstrakKUHP Nasional sebagai wajah baru hukum pidana Indonesia memberikan beberapa perubahan mendasar, antara lain ketentuan tentang asas legalitas materiil dan vicarious liability. Asas legalitas materiil memberikan ruang bagi living law untuk menjadi dasar pemberlakuan hukum pidana termasuk dalam menentukan pertanggungjawaban pidana. Vicarious liability merupakan salah satu bentuk pertanggungjawaban pidana yang meniadakan kesalahan dan diartikan sebagai pertanggungjawaban pengganti, yaitu setiap orang dapat dimintai pertanggungjawaban atas perbuatan orang lain. Perspektif living law hakikatnya sangat luas sehingga setiap masyarakat memilki karakteristik dan ketentuan yang berbeda. Ketentuan tentang vicarious liability berdasarkan living law salah satunya dapat dijumpai dalam angger perdata awal sebagai bentuk living law di Yogyakarta. Penelitian ini bertujuan untuk memberikan pemahaman terhadap pengaturan vicarious liability dalam hukum pidana Indonesia dan mengkaji pengaturan vicarious liability berdasarkan perspektif living law yang terdapat dalam angger perdata awal. Penelitian ini merupakan penelitian yuridis empiris dengan menggunakan pendekatan historis dan filosofis. Data yang digunakan dalam penelitian ini ialah data primer dan sekunder dengan menggunakan metode wawancara dan studi pustaka yang kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian ini menjelaskan adanya perbedaan pemahaman terhadap vicarious liability. Hukum pidana Indonesia melalui KUHP Nasional memahami vicarious liability hanya sebatas pertanggungjawaban “komando”, sedangkan perspektif living law dalam angger perdata awal memahami vicarious liability sebagai upaya untuk mewujudkan pemulihan keseimbangan dalam kehidupan kosmis yang dirusak oleh perbuatan seseorang. Rekomendasi dalam penelitian ini ialah perlu adanya penjelasan tambahan tentang vicarious liability dalam KUHP Nasional, sehingga selaras dengan living law.Kata Kunci: Angger Perdata Awal, Hukum Pidana Indonesia, Living Law, Vicarious Liability